Translating the regime: an insight into the history of translation during the Portuguese 20th century dictatorship - Chumbo, Isabel (2022)
This paper aims at presenting a contribution towards the history of translation during the 20th century in Portugal, from the perspective of exporting translations by the Estado Novo through the English speeches of António Oliveira Salazar in the period from 1933 to 1950. The work is based on a study which develops a comparative and descriptive project of a qualitative nature in order to contribute to the external and internal history of translation into English of Salazar’s speeches in the given context. The main objectives of this paper are: (1) to understand how translation within the Portuguese regime developed and worked; (2) to perceive the reasons why the regime translated into foreign languages, specifically into English; (3) to analyse and describe a corpus of translated texts, which allow us to establish a relation between translation and propaganda in the Portuguese context. Based on a thorough archival work, the study also describes the process surrounding these translations, as well as the agents involved. This contribution will provide a comparative perspective through the lens of translation and will undoubtedly shed light on the role translation played in the making of a specific historical period, especially when considering the diplomatic context and the behaviour the country assumed towards its external relations within Europe and the anglophone countries in particular. The analysed corpus will not only provide insight into the patterns and irregularities which occurred between the source and the English target texts, the choices the translators made, but also allow us to question the number and type of existing omissions in the English text. The accessed archives also justify some of the reasons why the texts were published with specific characteristics, thus leading to findings which clarify the position of translation within the dictatorial regime.